Indonesian Blue Economy for Sustainable Fisheries - Kumala Dewi, Yashinta; Aswar, Baso; Alam, Jamaluddin Fitra; Safruddin, Safruddin (Hasanuddin University, 2025)
Blue economy is a management system for all aquatic ecosystem resources, including marine and terrestrial ecosystems, related to economic value, sustainability of ecosystems and production resources, and distribution of benefits. The adoption of this concept in Indonesia uses the term inclusive and sustainable blue economy to emphasize the equitable distribution of benefits from the development of the blue economy by ensuring the sustainability of its carrying capacity. This paper explains the importance of managing Indonesian fisheries resources based on the blue economy concept to ensure the sustainability of existing fisheries resources. The literature study method issued by agencies and strategic stakeholders is the primary reference in this study. In this study, it was found that the significant challenges faced were the problem of environmental damage due to illegal activities such as illegal fishing, damage to mangrove forests, seagrass ecosystems, coral reefs, and production activities and the fisheries industry that often pays little attention to sustainability aspects so that it is deemed necessary to implement sustainable fisheries management policies that must focus on several urgent matters to achieve Indonesia's blue economy goals. Based on this, as a role model for research purposes, recommendations and research efforts have been made with a roadmap for the sustainable use of pelagic fisheries resources based on Indonesia's blue economy program in the Bone Bay area. Sustainable fisheries management based on the blue economy concept can be developed and applied well through collaboration and synergy with all existing stakeholders consisting of the government, universities, NGOs, and fishing communities.